Evaluación del tiempo y porcentaje de dos extractos enzimáticos naturales “bromelina y papaína” como ablandadores de músculo vacuno - Rodriguez Pincay, Lady Tatiana (2021)
This research aims to evaluate the time and percentage of two natural enzyme extracts "bromelain and papain" as a beef muscle softener. Time (6, 8 and 10 hours) and percentage of addition of each enzyme extract (30% and 50%) were evaluated. 12 treatments were used with 3 replicates, taking as an experimental unit 50g of cattle muscle, where the percentage of addition of each enzyme extract (30 and 50%) were manipulated. and the time (6, 8 and 10 hours) of action, the application of each extract was done by immersion. Texture profile parameters (hardness, elasticity, cohesivity, gummyness and chewability) were evaluated through the destructive method (puncture-penetration) using the Texturometer. The statistical design used was DCA (completely random design) with A*B*C trifactorial arrangement plus a witness. Dunnett's tests were able to identify the best treatment, with this being T10 (50% bromelain extract*10 hours) which showed the best texture profile.